Опуклості, породжені монадами - Радул, Т.M. (Видавничий дім "Академперіодика" НАН України, 2008)
Let F be a monad in the category Comp. We build a convexity in general sense for each F-algebra (see [1]), investigate properties of such convexities, and apply them to prove that the multiplication map of the monad of order-preserving functionals is soft.